Accountability in the economic and monetary union : foundations, policy, and governance - Markakis, Menelaos (Oxford : Oxford University Press, 2020)
Exploring the political and legal accountability of the Economic and Monetary Union and the Banking Union, this book focuses on how to render the EU and national institutions acting in this area more accountable and transparent in the exercise of their duties.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 23, 2020).
Keywords: Economic and Monetary Union; Law -- European Union countries; Government accountability -- European Union countries; Economics; Economics